Mitochondrial DNA in the bark weevils: size, structure and heteroplasmy - Boyce, T. M; Zwick, M. E; Aquadro, C. F (Genetics (Austin), 1989)
Mitochondrial DNA of higher animals has been described as an example of extreme efficiency in genome structure and function. Where exceptionally large size molecules have been found (>20 kb), most have occurred as rare variants within a species, suggesting that these variants arise infrequently and do not persist for long periods in evolutionary time. In contrast, all individuals of at least three species of bark weevil (Curculionidae: Pissodes) possess a mitochondrial genome of unusually large size (30-36 kb). The molecule owes its large size to a dramatically enlarged A+T-rich region (9-13 kb). Gene content and order outside of this region appear to be identical to that found in Drosophila. A series of 0.8-2.0-kb repeated sequences occur adjacent to the large A+T rich region and have perhaps played a role in the generation of the large size as well as an unprecedented frequency of size variant heteroplasmy. Every weevil sampled in all three species (n = 219) exhibits anywhere from two to five distinct size classes of mtDNA. The persistence of this large amount of size polymorphism through two speciation events combined with the abundant size variation within individuals suggests that these molecules may not be subject to strong selection for small overall size and efficiency of replication. This pattern of variation contrasts strongly with the conservation of gene content and arrangement in the coding region of the molecule.